Avaliação da qualidade da água mineral comercializada em postos de combustíveis no município de Goiânia. - Carvalho, Murilo Ferreira de (2015)
Water is a vital resource to life. The use of a water that does not offer risks to the health of the consumer is guaranteed by the law, however, there is a need to ensure, through the verification of some parameters, that the water is of good quality, and thus, the mineral water can appear as a safe option, and this fact is verified by continuous growth in demand for this type of product. The objective of this work was to analyze some of the parameters of quality of natural mineral water, bottled in gallons 20 liters which is marketed in fuel stations in the city of Goiania and compare them with the relevant legislation. Among the physical-chemical parameters were evaluated pH, conductivity, total dissolved solids, levels of nitrate and fluoride. And among the microbiological parameters were evaluated the total coliform and thermotolerant coliform. We collected 21 samples, in seven points of sale different, in the months of June, August and October 2014, for that would have a differentiation in the lots of the products. For the evaluation of the pH was used the potentiometric method, for the conductivity, the method of conductivity, for total dissolved solids the gravimetric method, for the levels of nitrate the spectrophotometric method and for the fluoride the selective ion electrode method. Total coliforms and thermotolerant coliforms were determinated by the technique of multiple tubes. All samples, except only one (4.76 %), were within the parameters required by law relative to microbiological analyses, certifying that the mineral water is of good quality. The sample that was not within the parameters, presented total coliforms, but the contamination by this type of bacterium, can be an indication that the hygienic and sanitary conditions during the production process were far below what is needed. In addition, with respect to the physical-chemical parameters, although the samples were within the standards of the law, the labels of the products showed a significant difference when compared with the results obtained. Therefore, it is important to have a continuous monitoring of sources of mineral water and also the monitoring of the parameters that attest to the quality of the products that reach consumers.